Intrapreneurship: Productive and Non-Productive. (September 2022) - Elert, Niklas; Stenkula, Mikael
Researchers increasingly recognize that entrepreneurial employees, intrapreneurs, play a critical role in innovation. As with regular entrepreneurship, however, the value of intrapreneurial activity depends on the firm-specific and societal reward structures that intrapreneurs face. Ideally, these rules of the game are such that they reward intrapreneurship that is beneficial for the firm and the economy. When this is not the case, intrapreneurship can be beneficial for the firm but not for society, damaging for the firm yet beneficial for society, or downright non-productive. We offer a taxonomy describing how society's rules and firm rules interact to produce different intrapreneurial outcomes.